Women and (their) children: wrongs, rights and relationships. Issue 6 (24th July 2017) - Van Praagh, Shauna; Campbell, Angela
ABSTRACT: As of the turn of the twenty-first century, a pregnant woman appears to be excluded from the Canadian private law of civil wrongs when it comes to any wrongfully inflicted harm on her own foetus. This article revisits and examines the images of pregnancy and maternity represented in the judgments in Dobson v. Dobson, a 1999 decision of the Supreme Court of Canada. Against the backdrop of contemporary discussions about surrogacy, the images put forth in Dobson – namely, the expecting woman, the autonomous woman and the woman as mother – represent more generally the co-existing and often entangled pictures with which the law grapples whenever pregnancy and maternity are at stake. This essay explores how we might imagine a more child-focused reflection of issues like those presented in Dobson . Without insisting on the applicability of children's rights as set out in conventions or charters, it is possible to include the interests and perspective of children in a nuanced analysis of law's engagement with pregnancy and maternity that does not compromise or erode women's rights or interests. Indeed, a recognition of children's interests in this context permits a juridical recognition of, and reconciling with, the complex and diverse realities of pregnancy and maternity.